(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2016)
This work was conducted to investigate the effect of oil type and lactic acid bacteria on the conjugated linoleic acid (CLA) production in MRS medium. The ability of eight strains of lactic acids bacteria; Lactobacillus acidophilus (P2, ATCC 20552), Lactobacillus brevis (P102), Lactobacillus casei (P9, DSMZ 20011), Lactobacillus plantarum (P1), Lactobacillus pentosus (P4), Lactobacillus rhamnosus (P5, TISTR 541), Bifidobacterium longum (BL) and Bifidobacterium lactis (P7, Bb-12) for the production of CLA in the MRS broth was investigated. Two vegetable oils (sun flower oil & linseed oil) and cod liver oil were used as substrates in MRS media. The oils were added to MRS in concentration of 10 mg/ml and incubated for three days at 37Â°C. The ability of lactic acid bacteria under the investigation as inhibitors were evaluated by the determination of the amount of conjugated linoleic acid at the end of the fermentation period. The results indicated that there were significant differences between the microorganisms in their ability to produce CLA. Furthermore, there were significant differences between oil types as substrate on the impact of CLA production. Bifidobacterium lactis showed the highest production of CLA (618.13 Âµg/ml) in MRS media fortified with cod liver oil. From the results, it can be concluded that there were positive impacts for both oils and lactic acid bacteria on the production of CLA. Therefore, the lactic acid bacteria grown in these oils can be utilized for probiotic production purposes and to produce other bioactive compounds.